2019
DOI: 10.1186/s12884-019-2644-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of anaemia in pregnant women receiving antenatal care at a tertiary referral hospital in Northern Ghana

Abstract: BackgroundAnaemia during pregnancy is a major public health problem in developing countries. It is important to regularly monitor haemoglobin level in pregnancy and factors associated with it to inform clinical and preventive services. The aim of this study was to assess the prevalence and determinants of anaemia in pregnant women attending antenatal clinic (ANC) of a tertiary referral hospital in Northern Ghana.MethodsAn analytical cross-sectional study involving 400 pregnant women receiving antenatal care in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
80
9
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 19 publications
25
80
9
10
Order By: Relevance
“…Although craving of nonfood substances in pregnant women was not associated with anemia in this study, the proportion of women who reported this food habit was high compared with a study done in Kenya, which found only 19.8% of pregnant women reported such nonfood cravings ( 27 ). The finding of this study is consistent with a study conducted in the Kilimanjaro Region in Tanzania ( 32 ) and in Ghana ( 40 ), in which 38% and 41.6% of pregnant women, respectively, had pica practices. None of these studies found an association between food craving habit and prevalence of anemia.…”
Section: Discussionsupporting
confidence: 92%
“…Although craving of nonfood substances in pregnant women was not associated with anemia in this study, the proportion of women who reported this food habit was high compared with a study done in Kenya, which found only 19.8% of pregnant women reported such nonfood cravings ( 27 ). The finding of this study is consistent with a study conducted in the Kilimanjaro Region in Tanzania ( 32 ) and in Ghana ( 40 ), in which 38% and 41.6% of pregnant women, respectively, had pica practices. None of these studies found an association between food craving habit and prevalence of anemia.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a 42.4% prevalence of anemia among pregnant women is in keeping with the global estimate of more than 40% [10], the prevalence of anemia among pregnant women in this study was 42.4%. This finding is similar to the 40.8-54.0% prevalence reported in Ghana [25,37,38], 40.0% in Ethiopia [39], 40.1% in Mali [35], 42.7% in South Africa [40] and 47.4% in Tanzania [41]. Importantly, the prevalence of mild, moderate and severe anemia were 35.7%, 6.1% and 0.6%, respectively.…”
Section: Plos Onesupporting
confidence: 87%
“…The prevalence of anaemia as seen in this study was 30.66% it is an indication that anaemia during pregnancy is still a major problem. The prevalence was comparable with what was obtained in similar studies of Nepal (42.5%), 12 Haryana (51%) 5 .The study findings are however in contrast to reports from other countries, 66% in Burkina Faso Meda et al, 13 50.8% in Anthony Wemakor et al(Ghana), 14 Jharkhand (76%). 15 It is suggested that the variations may be attributed to different causes of anaemia and dietary differences, population differences, study design and difference in methodology used in determining haemoglobin levels.…”
Section: Discussionsupporting
confidence: 85%